Recent disturbance events recorded in the sedimentary infill of Lago Guillelmo (Argentina): tephra falls and hydrogeomorphic processes (Latin American Journal of Sedimentology and Basin Analysis, 2023)
We studied two natural disturbances that affect the Parque Nacional Nahuel Huapi area: tephra fall  events from Andean volcanoes and hydrogeomorphic processes within catchments related to heavy rains. We carried out a surfaceanalysis, describing the main morphometric features of the selected watershed, informally called La Cantera watershed; analyzing satellite images and historical aerial photographs; looking for evidence of processes related to these disturbance events in the watershed and morphological changes in the alluvial fan generated over the delta. The subaqueous environment was analyzed through bathymetries,sediment cores, and Ground Penetrating Radar (GPR) profiles, taken in the distal deltaic environment of the watershed. In the sedimentary record of the lake, weidentified 12 tephra layers deposited in the last 200 years, attributed to Cordón Caulle, Calbuco, and Osorno volcanoes. These were chronologically correlated with previously documented eruptions of these volcanic centers, using vitroclast morphology, mineral association, and stratigraphic position. We also identified 10 epiclastic layers corresponding to sediments with terrigenous components and terrestrial organic matter, interpreted as hyperpycnites. We assign two hyperpycnite deposits to a debris flow that occurred in the area in February 2015 that caused several damages and roadblocks, based on the stratigraphic position of these deposits in the cores, and the identification of sediments associated with this event on the lake surface in satellite images. After the correlation between the GPR radargram units with the lacustrine cores, we associated one major radar unit with a (1) tephra layer and (2) lobe-shaped morphologies, interpreted as a hyperpycnite deposits, located in front of the outflow of an abandoned river course. The results allow inferring a significant anthropic impact in the lacustrine record, as a result of the construction of Route 40 and gravel mining activities after 1969 that affected the distal drainage network of the La  Cantera watershed, generating topographic lows that make it difficult for subaerial flows to reach the lake. This work shows the importance of the integration between subaerial processes that occur throughout a basin with the underwater processes that take place in the deltaic environment, to understand the  extension and characteristics of these natural disturbances.
Keywords: disturbances; Lago Guillelmo; lacustrine sedimentation; tephras; hyperpycnites